Determinants of successful virtual teams with special reference to the information technology sector in sri lanka - Dewage, V.D.; Alwis, A.C.D. (University of Jaffna, 2022)
Purpose: Technological advancements, globalization, and crisis situations have compelled society to adopt a virtual platform. In light of this scenario, the purpose of this study was to ascertain the determinants that influence the success of virtual teams and to identify the impact of each determinant on the success of virtual teams' relation to the Sri Lankan context in order to the benefits of the virtual platform. Methodology:This was a quantitative, cross-sectional study involving employees in the Information Technology (IT) sector. The data collection technique used was a structured questionnaire combined with a simple random sampling technique. Findings: This study will be a foundation for future researches current topic area. Correlation and multiple regression analysis were used to analyse the data. The research reveals that trust, leadership, and communication all have a significant positive impact on successful virtual teamwork, while ensuring a positive relationship between the variables. Implications: The uniqueness of this study is demonstrating how those factors contribute to the conversion of traditional teams to modern teams, by increasing the likelihood of the final outcome in a fruitful manner.
Keywords: Virtual teams; Globalization; Trust; Leadership; Communication